Skin, meaning, and symbolism in pet memorials : tattoos, taxidermy, and trinkets - Harris, Racheal (Emerald studies in death and culture., 2019)
In response to increased academic interest in the fields of death studies, memorial studies, and human and animal studies, Skin, Meaning and Symbolism in Pet Memorials examines the mourning rituals which exist between people and their domestic pets.Paying close attention to the changing role and increased prominence of the companion animal in the domestic setting, each chapter considers a different form of companion animal memorialization, linking modern practices such as tattooing to historical examples of animal focused memento mori, particularly taxidermy. The final chapter adopts a forward focus in its provision of a framework for future studies related to how death and memorialization rituals are increasingly coming to occupy the digital space. While skin and touch are the focal points of many encounters explored in the text, what becomes evident is how the virtual realm is increasingly intruding into the touch experience. As a result, the posthumous, online afterlives of pets are set to become a social issue of increasing significance to the death and mourning experience. This work meets the needs of academics, post-graduate students and general readers alike, appealing to anyone with an interest in death studies, popular culture, tattooing and human and animal studies.